Closed‐loop performance metrics for fault detection and isolation filter and controller interaction. (23rd December 2011) - Pandita, Rohit; Bokor, József; Balas, Gary
SUMMARY Fault detection and isolation (FDI) filters are typically synthesized for open‐loop or closed‐loop systems. The controller affects the FDI filter performance in the closed‐loop system. FDI filter performance and closed‐loop controller–filter interaction in the presence of uncertain dynamics were investigated as was the role of controller robustness on the FDI filter performance. The NASA Generic Transport Model aircraft was considered as a motivating application. Multiple example scenarios were presented to highlight the utility of FDI filter performance metrics. For example, comparing fault detection performance of different filters under identical uncertain plant dynamics and controller, the effect of different controllers on the FDI filter performance, and the effect of model uncertainty on filter performance. The Generic Transport Model aircraft FDI filter results are validated using worst‐case analysis and linear simulations. Copyright © 2011 John Wiley & Sons, Ltd.